The scale of zebrafish pectoral fin buds is determined by intercellular K+ levels and consequent Ca2+-mediated signaling via retinoic acid regulation of Rcan2 and Kcnk5b. - Xiaowen Jiang; Kun Zhao; Yi Sun; Xinyue Song; Chao Yi; Tianlong Xiong; Sen Wang; Yi Yu; Xiduo Chen; Run Liu; Xin Yan; Christopher L Antos (PLoS Biology)
K+ channels regulate morphogens to scale adult fins, but little is known about what regulates the channels and how they control morphogen expression. Using the zebrafish pectoral fin bud as a model for early vertebrate fin/limb development, we found that K+ channels also scale this anatomical structure, and we determined how one K+-leak channel, Kcnk5b, integrates into its developmental program. From FLIM measurements of a Förster Resonance Energy Transfer (FRET)-based K+ sensor, we observed coordinated decreases in intracellular K+ levels during bud growth, and overexpression of K+-leak channels in vivo coordinately increased bud proportions. Retinoic acid, which can enhance fin/limb bud growth, decreased K+ in bud tissues and up-regulated regulator of calcineurin (rcan2). rcan2 overexpression increased bud growth and decreased K+, while CRISPR-Cas9 targeting of rcan2 decreased growth and increased K+. We observed similar results in the adult caudal fins. Moreover, CRISPR targeting of Kcnk5b revealed that Rcan2-mediated growth was dependent on the Kcnk5b. We also found that Kcnk5b enhanced depolarization in fin bud cells via Na+ channels and that this enhanced depolarization was required for Kcnk5b-enhanced growth. Lastly, Kcnk5b-induced shha transcription and bud growth required IP3R-mediated Ca2+ release and CaMKK activity. Thus, we provide a mechanism for how retinoic acid via rcan2 can regulate K+-channel activity to scale a vertebrate appendage via intercellular Ca2+ signaling.